A review of Acianthera subgenus Brenesia (Orchidaceae, Pleurothallidinae), with a new species from Mexico - Solano , Rodolfo; Karremans, Adam P. (Instituto de Ecología, A.C., 2023)
Background and Aims: Brenesia was originally proposed to accommodate an odd taxon among the Orchidaceae subtribe Pleurothallidinae. This species is characterized by its sessile leaves, secondary stems covered by inflated sheaths and, especially, by a raceme produced at the base of the secondary stem. A few more closely related taxa were discovered afterwards, but the generic name has mostly been placed under the synonymy of Pleurothallis. Recent DNA-based studies showed that Brenesia constitutes a monophyletic group within the genus Acianthera. We present here a review of Acianthera subgenus Brenesia, delimiting each species in the group and providing a key for their identification. Methods: Specialized literature, specimens deposited in scientific collections, in cultivation, or available at online databases were reviewed. For each species, their known localities were georeferenced and displayed on a map of Mexico and Central America using QGIS software; also, their conservation status was assessed according to the IUCN Red List. Key results: Acianthera subg. Brenesia includes five species distributed from central Veracruz, Mexico, to Panama. The species included in this group are Acianthera costaricensis from Costa Rica and Panama; A. herrerae from Chiapas, in Mexico, and Guatemala; A. johnsonii from Chiapas to Honduras; and A. sotoana from (Mexico) Veracruz and Oaxaca. For each taxon, a morphological description, drawing, photo, information concerning nomenclature, distribution, habitat, phenology, and comparison with similar taxa are provided. Acianthera rzedowskiarum is described as a new species from Chiapas, based on specimens previously confused with A. johnsonii. Conclusions: Acianthera subgenus Brenesia has a distribution restricted to Central America. Four of its five species are native to Mexico, and one is restricted to southern Central America.